2022
DOI: 10.1097/ju.0000000000002692
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Institutional Experience in Single-Port Robotic Transvesical Simple Prostatectomy for Benign Prostatic Hyperplasia Management

Abstract: Purpose: Single-port (SP) robotic-assisted simple prostatectomy (RASP) through the transvesical approach is a novel surgical option in the management of large prostatic glands. We present the first multi-institutional study to further assess the perioperative and postoperative outcomes of SP RASP. Materials and Methods: From February 2019 to November 2021, 91 consecutive patients of 3 separate institutions underwent transvesical RASP using the da VinciÒ SP robotic surgical system. Surgeries were performed by 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…However, a multicentric study evaluating outcomes of SP RASP demonstrated that mean EBL was 100 cc, catheter days were approximately 5 days, though this was variable between institutions performing this procedure. Additionally, this study noted the practice of same day discharge after SP RASP 28 . Our institution routinely performs same day surgery for these patients, and patients are discharged with minimal to no narcotics.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a multicentric study evaluating outcomes of SP RASP demonstrated that mean EBL was 100 cc, catheter days were approximately 5 days, though this was variable between institutions performing this procedure. Additionally, this study noted the practice of same day discharge after SP RASP 28 . Our institution routinely performs same day surgery for these patients, and patients are discharged with minimal to no narcotics.…”
Section: Discussionmentioning
confidence: 95%
“…The utilization of the purpose‐built SP access port system allows for improved use of the “floating dock technique.” This provides increased working surgical space, in particular in small surgical fields with a close surgical target 28,29 . Furthermore, the access port allows for a smaller cystotomy as the size of the cystotomy need only accommodate the Alexis retractor component of the access port, and the combined width of the instruments, which enter the bladder with a combined diameter of less than 2.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Benson and Brandes for their interest and thoughts regarding our study entitled "Contrast-Enhanced Ultrasound and Shear Wave Elastography: Novel Methods for the Evaluation of Urethral Stricture Disease." 1 As fluoroscopic retrograde urethrogram has its limitations when characterizing urethral strictures, we conducted this pilot study to evaluate contrast-enhanced sonourethrography (CEUS SUG) and shear wave elastography (SWE) as novel methods in evaluating urethral strictures and have found potentially promising results using both modalities.…”
mentioning
confidence: 99%
“…Ye Tian, 1 Heng Zhang 1 and Guangheng Luo 1 * 1 Department of Urology, Guizhou Provincial People's Hospital, Guiyang, China *email: luoguangheng1975@163.com.…”
mentioning
confidence: 99%
“…For decades, open simple prostatectomy has represented the gold standard care for benign prostatic obstruction when large prostatic adenomas were encountered. 2 Growing evidence showed that when compared to open simple prostatectomy, RASP offered lower blood loss, a lower risk of blood transfusion and shorter hospital stays, 3 which was embraced by increasing adopters for its safety, efficacy and reproducibility. 4 The European Association of Urology guidelines, however, have clearly defined the ranking and have placed holmium laser enucleation of the prostate first for several years.…”
mentioning
confidence: 99%